Curbing illegal gold mining in Barberton - Mphokane, Shoki Ditabeng (My University, 2018)
In the more recent past Barberton has seen an increase in illegal gold mining activities and apparent lack of governance mechanisms by local government institutions to address the problem. This study focuses on examining and analysing the problem of illegal gold mining activities and reflecting on possible mechanisms that can explain mitigating aspects to reduce illegal gold mining. The study examines governance of state institutions (multi-agency departments) in addressing illegal mining at Barberton gold mines. The research used the qualitative approach to assist in understanding the complexity related to illegal gold mining in Barberton. The study is both descriptive and explanatory. For data collection, the study used in-depth interviews and documentary analysis. The study reveals persistent lack of coordination (with regard to support, team work and transparency), capacity (with regard to human, communication, equipment, transport and finance) and commitment (around patriotism, job satisfaction and effectiveness) by the institutions that should deal with the problematic of mining. The study concludes that success in the governance mechanisms of public institutions in Barberton essentially requires the integration or interface of the triple c’s (capacity; commitment and coordination). The study also concludes that there is a positive relationship between governance (in the form of integration of the triple c’s) and enclavity (structural marginalization of labour) while on the other hand advocating a negative relationship between governance (with regard to governance that is in distress) and the diffusion of responsibility (with regard to who will act accordingly to ensure the integration of the triple c’s). This study contends that when governance within necessary institutions is in distress and there is no intervention through the integration of the 3c’s, the diffusion of responsibility will come into place, as there will not be accountability. This study helps in understanding and explaining the challenges of service rendered by the Barberton multi-agency departments and reflects on how governance underpins the efforts to address illegal mining.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the Degree of Doctor of Philosophy, October 2018
Keywords: Illegal aliens--South Africa--Social conditions; Emigration and immigration--Government policy